The vascular anatomy of the forehead related to forehead flaps and its application in plastic and reconstructive surgery - Kleintjes, Wayne George (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Surgical Sciences))—University of Stellenbosch, 2007.